Flow field analysis and performance study of claw hydrogen circulating pump in fuel cell system. (6th October 2021) - Dong, Kairui; Liu, Guangbin; Yang, Qichao; Zhao, Yuanyang; Li, Liansheng; Gao, Zhicheng
Abstract: Hydrogen circulation pump is an important equipment for hydrogen fuel cell system which can recycle the unreacted hydrogen to improve the system efficiency. A mathematical model of claw pump is built and the internal flow field was simulated by dynamic mesh technology. The p- θ diagram is obtained by analyzing the gas flow characteristics. The model is firstly verified by air experiments and then the performance influenced by suction pressure, exhaust pressure, rotating speed, and clearance are analyzed. The volumetric efficiency increased by 22% when the suction pressure increases from 152 kPa to 168 kPa but decreased by 23% when the exhaust pressure increases from 172 kPa to 188 kPa. The volumetric efficiency increased by 26.7% when the rotating speed increases from 4000 rpm to 6000 rpm but decreased by 52.1% when the working clearance increases from 0.03 mm to 0.07 mm. Due to the range of working pressure ratio is small, the indicated efficiency changes slightly. Graphical abstract: The claw-type hydrogen circulating pump is suitable for hydrogen recovery in fuel cell system due to its stable gas transmission capacity, high efficiency, good force performance. The mathematical model is built to simulate the internal flow field. The actual working process is analyzed from the p - θ diagram. The pressure fluctuates in the suction and exhaust process and increases significantly in the isochoric process because of the hydrogen leakage. The indicative efficiency decreases with the increase of the exhaust loss. Image 1 Highlights: The mathematical model of claw-type hydrogen circulating pump in fuel cell is built to simulate the internal flow field. An air experiment is used to verify the simulation method. The working process is analyzed from the p-θ diagram. The performance influenced by operating conditions is detailed discussed.